2018
DOI: 10.1177/0266382118760143
|View full text |Cite
|
Sign up to set email alerts
|

The influence of shadow IT usage on knowledge sharing

Abstract: Employees increasingly use unauthorized technologies at the workplace, which is referred to as shadow IT. Previous research identifies that shadow IT is often collaborative systems used by employees to collaborate, communicate, and share content with coworkers, clients, or external partners. Based on these previous findings, we propose that shadow IT usage may positively influence organizational knowledge sharing (KS), which is central to knowledge management practices. Thus, this research aims to (1) identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 26 publications
1
28
0
1
Order By: Relevance
“…In general, shadow IT is a workaround where end users increase their efficiency and want to facilitate their day-to-day activities. Mallmann et al [53] divided the occurrences of shadow IT in accordance with device owner and software/solutions. According to their opinion, applications that represent shadow IT can be installed on devices that are owned by the company or the end users themselves.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, shadow IT is a workaround where end users increase their efficiency and want to facilitate their day-to-day activities. Mallmann et al [53] divided the occurrences of shadow IT in accordance with device owner and software/solutions. According to their opinion, applications that represent shadow IT can be installed on devices that are owned by the company or the end users themselves.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This part of shadow IT can be categorized under End user development. Finally, Mallmann et al [53] also add the category of IT usage through cloud services ( Figure 2). Therefore, shadow IT requires much less knowledge and experience in relation to end user development [11].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, shadow IT, often being collaborative technologies, can also mediate the relationship between social presence and individual impacts. Increasing the sense of social presence by using shadow IT can provide several benefits to employees in their work, such as permitting real-time communication, which facilitates information exchange and decision making [10; 25], enabling faster and better collaboration [8], and supporting knowledge sharing among employees [9]. All these individual impacts related to the greater perception of social presence promoted by shadow IT usage directly or indirectly enhance task performance [34].…”
Section: Social Influence and Social Presence Explaining The Individumentioning
confidence: 99%
“…The use of spreadsheets belongs to a much broader area, often referred to in literature as shadow IT, and denotes IT which is not under the control of IT departments. Shadow IT includes different artefacts developed or procured without the knowledge, approval or support of the IT department (Huber et al, 2017;Silic and Back, 2014;Rentrop and Zimmermann, 2012;Behrens, 2009;Spierings et al, 2012;Tambo et al, 2014;Haag and Eckhardt, 2017;Mallmann et al, 2018). Due to their availability and usability (Raković, 2014) spreadsheets feature as one of the main manifestations of shadow IT (Zimmermann et al, 2017) Zimmerman et al (2017 identified that shadow IT should be managed through re-engineering, coordination and registration from the aspects of risk and scope of such IT solutions.…”
Section: Introductionmentioning
confidence: 99%